Implementasi Kompresi File MP3 dengan Menerapkan Algoritma Levenstein - Anggraeni, Lenita Cahya; Hastawan, Ahmad Fashiha; Djuniadi, Djuniadi (Jurnal Ilmiah SINUS, 2024)
MP3 is an audio format that is often used because the data stored in MP3 format resembles the actual data when recorded.Storage space requirements will also rise if you keep a large number of MP3 files. Because of this, MP3 files must be compressed in order to prevent the storage space from filling up too quickly. This is because the compressed data will be lower in size. The Lossless compression method can be used to compress audio. The author uses the Levenstein Algorithm to implement audio compression in MP3 format. Levenstein's algorithm compresses data without any loss. When a file is compressed using lossless compression, the resulting file has the exact same size as the original file upon decompression. The author will be able to assess the effectiveness of MP3 file compression by using the Levenstein Algorithm to compress MP3 files. This will allow for faster transmission times and less data storage space consumption because the compressed MP3 file will shrink from its initial large size. After compression, the MP3 file's size—which was originally 128 bits—was reduced to 104 bits, yielding an 81.25% compression ratio. The purpose of this computation is to determine whether the compressed files are similar enough to be either decompressed or restored to their original size.